Correlation of structure, electrical conductivity, and oxygen permeability in strontium cobaltite ceramic membranes. Issue 4 (1st October 2020) - Jaiswal, Shivendra Kumar; Kashyap, Vijay Kumar; Kumar, Jitendra
ABSTRACT: An attempt has been made to synthesize a highly stable oxygen-deficient strontium cobaltite SrCoO3-δ (δ = 5/16) by decomposition of the sol-gel derived oxalate at 1000°C for 10 h in air. The product corresponds to the rhombohedral Sr6 Co5 O15 (93 wt%) and spinel cubic Co3 O4 (7 wt%) phases at room temperature but displays the perovskite-type cubic structure with a 3.953 Å at 900°C. It serves as an excellent material for separation of oxygen from the air and exhibits high oxygen permeability (JO2 ) of 3.0 ml/cm 2 .min at 1000°C for a 1.0 mm thick membrane. The activation energy of the process is found as 22 kJ/mol. Further, both JO2 and conductivity (σ) reveal good correlation with phases present at different temperatures. The system shows (i) reversible phase separation following the reaction SrCoO3-δ →Sr6 Co5 O15 + Co3 O4 and (ii) hysteresis in oxygen permeability upon cooling but remains reusable.